Medical Qigong for Cancer Patients: Pilot Study of Impact on Quality of Life, Side Effects of Treatment and Inflammation - Oh, B.; Butow, P.; Mullan, Barbara; Clarke, S. (World Scientific Publishing, 2008)
Quality of life (QOL) of cancer patients is often diminished due to the side effects of treatment and symptoms of the disease itself. Medical Qigong (coordination of gentle exercise and relaxation through meditation and breathing exercise based on Chinese medicine theory of energy channels) may be an effective therapy for improving QOL, symptoms and side effects, and longevity of cancer patients. In this pilot study, the feasibility, acceptability, and impact of Medical Qigong (MQ) were evaluated on outcomes in cancer patients. Thirty patients diagnosed with heterogeneous cancers, were randomly assigned to two groups: a control group that received usual medical care and an intervention group who participated in a MQ program for 8 weeks in addition to receiving usual medical care. Randomization was stratified by completion of cancer treatment (n = 14) or under chemotherapy (n = 16). Patients completed measures before and after the program. Quality of life and symptoms were measured by the EORTC QLQ-C 30 and progress of disease by the inflammation biomarker (CRP: c-reactive protein) via a blood test was assessed. The MQ intervention group reported clinically significant improved global QOL scores pre- and post-intervention. The MQ intervention also reduced the symptoms of side effects of cancer treatment and inflammation biomarker (CRP) compare to the control group. Due to the small sample size, however, the results were not statistically significant between treatment and the control groups. Data from the pilot study suggest that MQ with usual medical treatment can enhance the QOL of cancer patients and reduce inflammation. This study needs a further investigation with a larger sample size.